Beyond sub-Rayleigh imaging via high order correlation of speckle illumination. (18th October 2019) - Li, Fu; Altuzarra, Charles; Li, Tian; Scully, M O; Agarwal, G S
Abstract: Second order intensity correlations of speckle illumination are extensively used in imaging applications that require going beyond the Rayleigh limit. The theoretical analysis shows that significantly improved imaging can be extracted from the study of increasingly higher order intensity cumulants. We provide experimental evidence by demonstrating resolution beyond what is achievable by second order correlations. We present results up to 25th order. We also show an increased visibility of cumulant correlations compared to moment correlations. Our findings clearly suggest the benefits of using higher order intensity cumulants in other disciplines like astronomy and biology.